Report on the mineral statistics of the island [electronic resource] - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. (St. John's Nfld. : Robinson, 1917)
Table. At head of title: Geological Survey of Newfoundland. "For the year 1901." Electronic reproduction. Mode of access: Internet. 44